Performance of the SAC-C satellite electricity storage system - Garaventta, Guillermo Norberto (2012)
The analysis of telemetry data of the Argentine electricity storage system SAC-C satellite is presented. Diagnostic indicators were established in order to evaluate the in-flight performance of the satellite nickel-hydrogen batteries. The state of charge of the batteries was related to the hydrogen pressure. A predictive analysis allowed us to detect early failure of the electricity storage system.